A 490 W transversely excited atmospheric CO2 spark gap laser with added H2. (22nd January 2018) - Zand, M; Koushki, A M; Neshati, R; Kia, B; Khorasani, K
Abstract: In this paper we present a new design for a high pulse repetition rate transversely excited atmospheric CO2 laser with ultraviolet pre-ionization. A new method of fast thyristor capacitor charging and discharging by a spark gap is used. The effect of H2 gas addition on the output and stability of a transversely excited atmospheric laser operating with a basic mixture of CO2, N2 and He is investigated. The output power was increased by adding H2 to the gas mixture ratio of CO2 :N2 :He:H2   =  1:1:8:0.5 at total pressure of 850 mbar. An average power of 490 W at 110 Hz with 4.5 J per pulse was obtained. The laser efficiency was 11.2% and oxygen gas was used in the spark gap for electron capture to reduce the recovery time and increase the repetition rate.